Analisis Peningkatan Indeks Pembangunan Bidang Kesehatan di Provinsi Banten - Agus Sjafari; Kandung Sapto Nugroho; Arenawati Arenawati (JIPAGS (Journal of Indonesian Public Administration and Governance Studies), 2020)
Based on the research conducted showed that the achievement of Serang District IPKM get value 0.7709, then the achievements IPKM Pandeglang get value 0.7575, achievement IPKM Cilegon City get value 0.8491, and the achievement of Tangerang City IPKM get value 0.8622. Four districts / cities that become the focus of this study all of which showed an increase of IPKM in the previous year. Some research recommendations are as follows: 1). Instilling public awareness of hygienic behavior and healthy (PHBs), 2) Collecting regions access to clean water minimal, and supply of clean water through community empowerment programs, 3) It should be disseminated oral health and dental examination and oral routine. 4) The need for a redistribution of the distribution of health personnel, 5) Optimizing the anti-smoking movement, especially in young children to reduce smoking behavior., 6) Control Card Healthy Indonesia, and 7) Support morally and politically to the establishment of the Faculty of Medicine in order to increase access to health workers lead to improvements in Banten in particular HDI HDI Health Affairs.Keyword: improvement, Health Sector Development Index